2011
DOI: 10.2337/db10-1809
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of Cannabinoid Receptor Type 2 in a Mouse Model of Diabetic Nephropathy

Abstract: OBJECTIVEThe cannabinoid receptor type 2 (CB2) has protective effects in chronic degenerative diseases. Our aim was to assess the potential relevance of the CB2 receptor in both human and experimental diabetic nephropathy (DN).RESEARCH DESIGN AND METHODSCB2 expression was studied in kidney biopsies from patients with advanced DN, in early experimental diabetes, and in cultured podocytes. Levels of endocannabinoids and related enzymes were measured in the renal cortex from diabetic mice. To assess the functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
168
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(178 citation statements)
references
References 45 publications
7
168
3
Order By: Relevance
“…These changes are likely mediated by internalization of albumin and are not regulated by ERK1/2 signaling [52]. While CB 2 receptor expression is unaffected in STZ-induced diabetic mice and rats [51,52], its glomerular expression is downregulated in patients with advanced DN [51]. This observation could be explained by increased intraglomerular pressure, but not renal hyperglycemia.…”
Section: Role Of Cb 2 Receptor In Dnmentioning
confidence: 68%
See 3 more Smart Citations
“…These changes are likely mediated by internalization of albumin and are not regulated by ERK1/2 signaling [52]. While CB 2 receptor expression is unaffected in STZ-induced diabetic mice and rats [51,52], its glomerular expression is downregulated in patients with advanced DN [51]. This observation could be explained by increased intraglomerular pressure, but not renal hyperglycemia.…”
Section: Role Of Cb 2 Receptor In Dnmentioning
confidence: 68%
“…Unlike a previous study by the same group, global deletion but not pharmacological CB 2 receptor activation regulates renal fibrosis. In their earlier study, Barutta et al [51] demonstrated that AM1241 does not ameliorate renal fibrosis, while their recent findings show that the expressions of fibronectin, type I collagen, and type IV α4 chain collagen are further enhanced in CB 2 -null diabetic mice [73], suggesting that pharmacological modulation of CB 2 receptor by AM1241 is not sufficient to protect against renal fibrosis. To clarify how monocyte infiltration could be a potential mediator in the genetic absence of CB 2 receptor and indirectly affects kidney function by releasing cytokines and reactive oxygen species (ROS), it is found that transplantation of CB 2 -null bone marrow cells does not magnify albuminuria, renal dysfunction, and/or fibrosis in STZtreated wild-type animals [73].…”
Section: Role Of Cb 2 Receptor In Dnmentioning
confidence: 96%
See 2 more Smart Citations
“…There is emerging evidence that activation of CB2 inhibits tissue inflammation and has analgesic properties [78][79][80]. The CB2 subtype is mainly expressed outside the CNS, as described earlier, so it can act as a potential endocannabinoid target where analgesic effects may be separated from psychotropic effects by activating the peripheral receptors.…”
Section: Cannabinoid Receptors As Therapeutic Targetsmentioning
confidence: 99%